Evaluasi Strategi Badan Pendapatan Daerah dalam Meningkatkan Pembayaran Pajak Restoran di Kabupaten Sikka - Maria Febrianti Doa; Cicilia Ayu Wulandari Nuwa; Margaretha Yulianti (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2025)
This research discusses the strategies implemented by the Sikka Regency Regional Revenue Agency (Bapenda) in increasing restaurant tax payments. Restaurant tax is one of the sources of Regional Original Revenue (PAD) that plays an important role in regional development. However, restaurant tax collection still faces various obstacles, such as low levels of taxpayer compliance, lack of education and socialization, and weak supervision and law enforcement. This research uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation studies. The results showed that Bapenda of Sikka Regency implemented three main strategies to increase restaurant tax payments, namely conducting socialization to business actors, conducting petition tests to test the level of taxpayer compliance, and installing online recording devices (M-Pos) to monitor transactions. Although these strategies have been implemented, their effectiveness is still limited due to the lack of regulations governing the use of M-Pos and low taxpayer participation in socialization activities. Based on data from 2019 to 2023, the realization of restaurant tax revenue only reached the target in 2019 and 2020, while in subsequent years it decreased. Therefore, it is necessary to increase education, strengthen regulations related to the use of M-Pos, and stricter supervision so that taxpayer compliance increases and the tax revenue target increases.